Conductive graphene as passive saturable absorber with high instantaneous peak power and pulse energy in Q-switched regime - Zuikafly, Siti Nur Fatin; Khalifa, Ali; Ahmad, Fauzan; Shafie, Suhaidi; Harun, Sulaiman Wadi (Elsevier, 2018)
The Q-switched pulse regime is demonstrated by integrating conductive graphene as passive saturable absorber producing relatively high instantaneous peak power and pulse energy. The fabricated conductive graphene is investigated using Raman spectroscopy. The single wavelength Q-switching operates at 1558.28 nm at maximum input pump power of 151.47 mW. As the pump power is increased from threshold power of 51.6 mW to 151.47 mW, the pulse train repetition rate increases proportionally from 47.94 kHz to 67.8 kHz while the pulse width is reduced from 9.58 μs to 6.02 μs. The generated stable pulse produced maximum peak power and pulse energy of 32 mW and 206 nJ, respectively. The first beat node of the measured signal-to-noise ratio is about 62 dB indicating high pulse stability.